Plant-Based Bioactive Natural Products: Insights into Molecular Mechanisms of Action - Devkota, Hari Prasad (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Medicinal plants have been used for the maintenance of human health since ancient times, in the form of food, spices, and traditional medicines. Medicinal plant-based traditional medicines serve as the primary healthcare systems in various countries even in recent times. Alongside this, medicinal plants have also served as the one of the main sources for the discovery of new therapeutic agents. At present, various plant extracts and their isolated phytochemicals are screened and evaluated for their diverse pharmacological activities related to both communicable and non-communicable diseases. However, comparatively little focus is given to the detailed mechanism of action of these agents on the molecular level. Molecular mechanism-based studies are essential for the development of evidence-based traditional medicines as well as for the development of isolated natural products as the lead candidates for novel drug discovery. This main focus of this Special Issue "Plant-based Bioactive Natural Products: Insights into Molecular Mechanisms of Action" is to cover the recent advances in science related to the molecular mechanisms of action of natural products. A total of nine articles were published in this Special Issue, including two original research articles and two review articles. This Special Issue has provided some new experimental data on bioactive natural products and their detailed mechanisms of action for biological activities. Similarly, review articles have provided state-of-the-art information on the related topics. I would like to thank all the authors for submitting their manuscripts and the reviewers and editors for their contribution to this Special Issue. Furthermore, I am also grateful to the handling editors and staffs of Applied Sciences for their support during the preparation and finalization of this Special Issue.